2003
DOI: 10.1046/j.1529-8817.2003.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

THE COMPLEX POLYSACCHARIDES OF THE RAPHID DIATOM PINNULARIA VIRIDIS (BACILLARIOPHYCEAE)1

Abstract: A combination of carbohydrate analysis and atomic force microscopy (AFM) was used to characterize the polysaccharides of the pennate diatom, Pinnularia viridis (Nitzsch) Ehrenberg. Polymeric substances were fractionated into those in the spent culture medium (SCM) and those sequentially extracted from the cells with water at 45° C (WW), NaHCO3 containing EDTA at 95° C (HB), and 1 M NaOH containing NaBH4 at 95° C. Carbohydrate, protein, and sulfate were detected in all the fractions, but their relative proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
127
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(138 citation statements)
references
References 52 publications
10
127
1
Order By: Relevance
“…The structure of the glucan was not elucidated, but proposed that the putative extracellular glucan served as an energy-reserve carbohydrate, possibly under the same control as chrysolaminaran. In a study of the total polysaccharides from a freshwater benthic diatom, Pinnularia viridis (Chiovitti et al, 2003), 1,3-linked glucans were found to be the dominant component of the extract obtained by treatment of thawed cells with water at 458C. Atomic force microscopy showed that the topography and properties of the cell surface mucilage of the diatom had been altered during warm-water extraction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the glucan was not elucidated, but proposed that the putative extracellular glucan served as an energy-reserve carbohydrate, possibly under the same control as chrysolaminaran. In a study of the total polysaccharides from a freshwater benthic diatom, Pinnularia viridis (Chiovitti et al, 2003), 1,3-linked glucans were found to be the dominant component of the extract obtained by treatment of thawed cells with water at 458C. Atomic force microscopy showed that the topography and properties of the cell surface mucilage of the diatom had been altered during warm-water extraction.…”
mentioning
confidence: 99%
“…willei), Chaetoceros sp., Skeletonema costatum and Stauroneis amphioxys (Ford & Percival, 1965;Handa & Yanagi, 1969;Myklestad & Haug, 1972;Smestad Paulsen & Myklestad, 1978;McConville et al, 1986). More recently, linkage analyses of water extracts obtained during sequential extraction of Achnanthes longipes (Wustman et al, 1997) and Pinnularia viridis (Chiovitti et al, 2003) yielded 1,3-linked glucopyranose (Glcp) as the dominant component.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many types of enzymes, such as oxidoreductases, transferases, hydrolase, lyase, isomerase, and ligase, have been reported to have antifouling capabilities [25,58,[97][98][99][100][101][102][103][104][105][106]. From the perspective of enzymatic antifouling technology, biofouling problems are caused by the formation and reproduction of biofilms, and the adhesion of spores and larvae of macroorganisms.…”
Section: Biological Methodsmentioning
confidence: 99%
“…Generally, polysaccharide degradation is executed by glycosylase. However, to degrade polysaccharides is difficult because the process is quite complex [106] and glycosylase can target only a limited range of linkages. Consequently, it would be difficult to choose an appropriate glycosylase for broadspectrum antifouling [103].…”
Section: Enzymes That Degrade Adhesives Used For Settlementmentioning
confidence: 99%